Impact of physician’s sex/gender on processes of care, and clinical outcomes in cardiac operative care: a systematic review - Louise Y Sun; Sylvain Boet; Amy Johnston; Katina Zheng; Mimi Deng; Fadi Mansour; Hussein Said; Cole Etherington (BMJ Open)
Objectives This systematic review aimed to assess the role of physician’s sex and gender in relation to processes of care and/or clinical outcomes within the context of cardiac operative care.Design A systematic review.Data sources Searches were conducted in PsycINFO, Embase and Medline from inception to 6 September 2018. The reference lists of relevant systematic reviews and included studies were also searched.Eligibility criteria for selecting studies Quantitative studies of any design were included if they were published in English or French, involved patients of any age undergoing a cardiac surgical procedure and specifically assessed differences in processes of care or clinical patient outcomes by physician’s sex or gender. Studies were screened in duplicate by two pairs of independent reviewers.Outcome measures Processes of care, patient morbidity and patient mortality.Results The search yielded 2095 publications after duplicate removal, of which two were ultimately included. These studies involved various types of surgery, including cardiac. One study found that patients treated by female surgeons compared with male surgeons had a lower 30-day mortality. The other study, however, found no differences in patient outcomes by surgeon’s sex. There were no studies that investigated anaesthesiologist’s sex/gender. There were also no studies investing physician’s sex or gender exclusively in the cardiac operating room.Conclusions The limited data surrounding the impact of physician’s sex/gender on the outcomes of cardiac surgery inhibits drawing a robust conclusion at this time. Results highlight the need for primary research to determine how these factors may influence cardiac operative practice, in order to optimise provider’s performance and improve outcomes in this high-risk patient group.